TEACHING PERFORMANCE IN THE CONTEXT OF INCLUSIVE EDUCATION: CHALLENGES AND POSSIBILITIES WITH STUDENTS WITH DISABILITIES - Juliane Barros Generoso, Cibele; Cristiane Barros Moreira, Érica (Revista Gênero e Interdisciplinaridade, 2023)
Understanding Education as a fundamental right of human beings may seem essential, but this recognition dates from a recent period. It was only in 1948, in the Universal Declaration of Human Rights established by the United Nations (UN) where Education was officially registered as an essential right for every citizen. Since then, the subject has been the subject of constant studies and approaches, among them that since it is a right for all, education must be inclusive, not restricted to just allowing common access, but in a way that every citizen , regardless of their characteristics, limitations or deficiencies, can receive a quality education that is adaptable to their needs. This article aims to reflect on special and inclusive education and the role of teachers with students with intellectual disabilities. As specific objectives, it is expected to conceptualize what intellectual disability is, and to understand the limits and possibilities of teaching, especially in the multifunctional resource room.